A CRITICAL DISCOURSE ANALYSIS OF NEWS REPORT FRAMING IN ANALISA AND SUMUT POS NEWSPAPER - Ilham Sahdi Lubis; Irma Khoirot Daulay; Bambang Nur Alamsyah; Rahmawati Rahmawati (Institut Pendidikan Tapanuli Selatan, 2023)
The current article provides a Critical Discourse Analysis (Forth, CDA) of news report of Corruption Eradication Commission (Forth, KPK). The same topic was reported in two different newspapers such as Analisa and Sumut Pos newspaper and was published on Sunday, 15th December 2014. Analisa and Sumut Pos newspaper are Local newspapers in Medan. The present study is done by using CDA perspective in order to explore the scope and nature of the two newspapers’ ideologies, for instance, to support or against the group of people or institution and how the reporters’ intervention is used in framing the news stories to make readers understand them in the way by the producer of the text. The methodology used is based on three elements in CDA’s analysis namely: Descriptive (Text analysis), Interpretation (Processing analysis) and Explanation (Social analysis). The finding shows how the hidden ideologies framed by the producer of the text. The study shows how language is used in constructing certain ideologies and how these ideologies exercise a great deal of power in shaping the local reader’s interpretation of the given facts. The perspectives presented tended to be in line with the beliefs held by the two newspaper’s target reader.